ANALISIS PENGARUH MODAL, TENAGA KERJA DAN TEKNOLOGI TERHADAP PRODUKSI INDUSTRI KAIN ENDEK DI KABUPATEN KLUNGKUNG - Indrayani, Gusti Ayu Made Oka; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 8 (2021): VOL 10 NO 8, AGUSTUS 2021 [3104 - 3527], 2021)
The industrial sector has a very important role, including the Balinese endek woven fabric industry. This study aims 1) To analyze the effect of capital, labor and technology simultaneously on the production value of the endek fabric industry in Klungkung Regency, 2) To analyze the effect of capital, labor and technology partially on the production value of the endek fabric industry in Klungkung Regency, and 3) To analyze the characteristics of endek fabric production in Klungkung Regency. The data used are primary data. The samples taken were 54, with regression analysis. The results of the study show that capital, labor and technology simultaneously affect the production value of endek fabrics in Klungkung Regency. Partially the variables of capital, labor and technology partially affect the production value of endek fabrics in Klungkung Regency. The value of ?1 = 0.215 <?2 = 8.194, then the production characteristic of the endek woven fabric industry in Klungkung Regency is labor-intensive. This means that for the production of endek woven fabrics, Klungkung Regency uses more labor than capital goods.   Keywords: Capital, Labor, Technology, Production